Work environmental motivation - a case study at the Association of Parents and Friends of the Exceptional in Dianópolis (APAE) (Research, Society and Development, 2021)
Motivation in the work environment has become popular among companies in search of a good quality of life for their employees, aiming at a good performance and profitability for the company. The present study has the general objective of analyzing the motivation in the work environment of the employees of the Association of Parents and Friends of the Exceptional of Dianópolis (APAE), in relation to the work environment. This research is predominant, qualitative and quantitative because the purpose of the research is to analyze the degree of motivation of the collaborators and involves a data collection with access to documents that was made available by the company to the researcher, the questionnaire with seven questions will be applied to 31 among them, teachers from the first to the fifth year, teachers from the first and second segment of EJA, coordinators, secretary, director, general services assistant, watchmen, cook and drivers of the Association of Parents and Friends of the Exceptional (APAE), with the in order to identify the factors that do not contribute to the motivation of employees, carried out from March to October 2020. In view of this research, it was possible to see that the hypothesis raised at the beginning of this work was partially confirmed, since the other respondents are satisfied with environment but are not 100% satisfied with their co-workers, and there is a conflict to be resolved by the institution.